Energy transition in developing countries - World Bank (Washington, 1983)
The developing countries are in a period of adjustment to higher world energy prices and increasingly widespread shortages of fuelwood and other traditional fuels. The recent decline in international energy prices and their shortages of fuelwood and other traditional fuels. The recent decline in international energy prices and their short term unpredictibility do not reduce the need to continue planning on the premise of increased energy prices in the longer term.
Keywords: Energy consumption-developing countries